Writing Program Architecture : Thirty Cases for Reference and Research - White-Farnham, Jamie; Finer, Bryna Siegel (Book collections on Project MUSE., 2017)
"Information and analysis concerning the material, logistical, and rhetorical features of a writing program, such as contracts, funding lines, and curriculum. Drawing from award-winning programs, the contributors analyze reporting lines, funding sources, jurisdiction of the writing program administrator (WPA), available majors, and other critical programmatic matters"--Provided by publisher